An Imaging Approach to Identify Mechanisms of Resistance to Pineapple Fruitlet Core Rot - Barral, Bastien; Chillet, Marc; Léchaudel, Mathieu; Lartaud, Marc; Verdeil, Jean-Luc; Conéjéro, Geneviève; Schorr-Galindo, Sabine (Frontiers in Plant Science, 2019)
Fruitlet core rot is a major postharvest disease of pineapple (Ananas comosus var. comosus). In the past, control programs were designed to eliminate symptoms without addressing their causes or mechanisms, thus achieving only moderate success. In this study: (i) we focused on the anatomy of the fruitlets in resistant ‘MD-2’ and susceptible ‘Queen’ pineapple cultivars; (ii) identified the key role played by the carpel margin in the infection process (iii) identified the key role played by the sinuous layer of thick-walled cells on the colonization inhibition of Fusarium ananatum; and (iv) linked the anatomy of the fruitlets with the phenolic content of cell walls. The fruitlet anatomy of the two cultivars was studied using X-ray, fluorescence and multiphoton microscopy. Sepals and bracts were not perfectly fused with each other, allowing the pathogen to penetrate the fruit even after flowering. In fact, the fungi were found in the blossom cups of both cultivars, but only become pathogenic in the flesh of ‘Queen’ pineapple fruit in natural conditions. The outer layer of the 'MD-2' cavity was continuous with thick cell walls composed of ferulic and coumaric acids. The cell walls of ‘Queen’ were less lignified at the extremities and the outer layer was interspersed with cracks. The carpel margins were fused all over in ‘MD-2’ contrary to ‘Queen’. This blemish allows the fungus to penetrate deeper in the susceptible cultivar. In pineapple fruitlets, hyphae of F. ananatum mainly progressed directly between cell walls into the parenchyma, but never reached the vascular region. The colonization was stopped by a layer of thick-walled cells in the case of the resistant cultivar, probably the infralocular septal nectaries. Anatomical and histochemical observations coupled with spectral analysis of the hypodermis suggested the role of lignin deposition in the resistance to F. ananatum. Coumaric and ferulic acids were shown to be the major phenolics bound to the cell walls and were found in higher amounts in the resistant cultivar post-inoculation. The combination of fruitlet anatomy and lignification plays a role in the mechanism of host resistance to fruitlet core rot.